Comparative Efficacy of Jaungo, A Traditional Herbal Ointment, and the Water-in-Oil Type Non-Steroidal Moisturizer for Radiation-Induced Dermatitis in Patients With Breast Cancer: A Study Protocol for a Prospective, Randomized, Single-Blinded, Pilot Study - Kim, Eun Hye; Yoon, Jee-Hyun; Park, Su Bin; Lee, Jee Young; Chung, Weon Kuu; Yoon, Seong Woo (Frontiers in Pharmacology, 2021)
Background: Radiation-induced dermatitis (RID) is a common complication of radiation therapy (RT). Although it has a high prevalence and can even trigger the premature end of conventional cancer therapies, there is no standard management. This study aims to evaluate whether topical use of Jaungo (Shiunko), a traditional herbal ointment mainly composed of Lithospermi radix and Angelica sinensis, could reduce RID compared to the water-in-oil type non-steroidal moisturizer in patients with breast cancer. Methods: This is a prospective, single-blinded, randomized controlled pilot trial that investigates the effect of topical application of Jaungo for the prevention of RID in postoperative breast cancer patients scheduled for RT, in comparison with the non-steroidal moisturizer, with a random distribution of 50 patients across the two groups. RT will be administered for 5–7 weeks with a biological equivalent dose (BED10) of 60 Gy or more, and the interventions will be applied 3 times a day during RT duration. Participants will be assessed a total of nine times, including eight visits during the period of RT and one visit at a 2-week follow-up period after the end of treatment. The incidence and severity of RID, quality of life, skin reaction symptoms, and maximum pain related to RID will be measured. The incidence rate of grade 2 or higher RID using the Radiation Therapy Oncology Group (RTOG) in the two groups will be statistically compared as the primary outcome. The types and frequencies of adverse events will be also collected and evaluated. All assessments will be performed by independent radiology oncologists. Discussion: This trial is currently ongoing and is recruiting. This study will determine the preventive efficacy of Jaungo in RID with postoperative breast cancer patients and provide evidence in traditional Korean medicine clinical practice.